Investigation of the hydraulic shock method of water lifting from watercourses - Sarkynov Yerbol; Zhakupova Zhanar; Ardakova Aizhan; Dyussenbiyeva Akerke (Research Reviews, 2024)
The most affordable type of water supply, which does not require high costs, are terrestrial water sources - natural and artificial, most of which can use kinetic energy of moving water as an energy source to drive alternative pumping units operating on energy-saving and environmentally friendly water lifting technology, allowing to increase the efficiency of mechanization of water supply for household and household needs of the agricultural consumer.